2018
DOI: 10.3389/fonc.2018.00494
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics of Non-muscle Invasive Bladder Cancer: Biomarkers for Early Detection of Bladder Cancer

Abstract: Background: Clinical outcomes of bladder cancer (BC) are tightly associated with the stage and grade of the initial diagnosis of BC because early detection is clearly important for patients with BC. However, the diagnostic capability of current detection methods, such as urinary cytology, cystoscopy, imageology method, and several urine-based tests, is inadequate for early detection of BC. The objective of our study is to discover novel biomarkers for detecting BC at an early stage, called non-muscle invasive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 39 publications
4
22
0
Order By: Relevance
“…Moreover, 3-hydroxy-cis-5-tetradecenoylcarnitine belongs to the carnitine group; carnitine and its short-chain derivatives are necessary for fatty acids to enter the mitochondria for oxidation. Cheng et al ( 2018 ) has shown that 3-hydroxy-cis-5-tetradecenoylcarnitine can be used as an important biomarker for the diagnosis of bladder cancer (AUC and sensitivity values of 0.899 and 0.881, respectively). Nevertheless, the diagnostic validity of 3-hydroxy-cis-5-tetradecenoylcarnitine in PTC requires further studies to confirm.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, 3-hydroxy-cis-5-tetradecenoylcarnitine belongs to the carnitine group; carnitine and its short-chain derivatives are necessary for fatty acids to enter the mitochondria for oxidation. Cheng et al ( 2018 ) has shown that 3-hydroxy-cis-5-tetradecenoylcarnitine can be used as an important biomarker for the diagnosis of bladder cancer (AUC and sensitivity values of 0.899 and 0.881, respectively). Nevertheless, the diagnostic validity of 3-hydroxy-cis-5-tetradecenoylcarnitine in PTC requires further studies to confirm.…”
Section: Discussionmentioning
confidence: 99%
“…Four such feature time series are depicted in Fig 7B, of all which have been highlighted by alternative methods. The urine-related metabolite 2-hydroxyethanesulfonate and pantothenol both displayed lower ion intensity levels in the multipurpose-use Building 1 than in the residential buildings; similarly 6-keto-decanoylcarnitine, a urine metabolite used in non-muscle invasive bladder cancer diagnostic models [32], was mostly absent in Building 1 but appeared at high levels in the other two ( Fig 7B). Such differences, for many features, in Building 1 relative to 2 and 3 may explain the ease of Building 1 classification.…”
Section: Machine Learning Classifies Buildings and Finds Building-spementioning
confidence: 94%
“…Four such feature time series are depicted in Figure 7B, of which three were highlighted by alternative methods (2-hydroxyethanesulfonate, pantothenol and ropinirole). The urine-related metabolite 2-hydroxyethanesulfonate and pantothenol both displayed lower ion intensity levels in the multipurpose-use Building 1 than in the residential buildings; similarly 6-keto-decanoylcarnitine, a urine metabolite used in non-muscle invasive bladder cancer diagnostic models 32 , was mostly absent in Building 1 but appeared at high levels in the other two ( Figure 7B). Beyond these four, many of the important metabolites were either stable and statistically significant between buildings, or possessed alternative unstable metabolite class labels (Tables S5 and S6).…”
Section: Single Day Feature Profiles Allow For Building Classificatiomentioning
confidence: 99%